Combinatorial hypofractionated radiotherapy and pembrolizumab in anaplastic thyroid cancer - Janice Ser Huey Tan; Timothy Kwang Yong Tay; Enya Hui Wen Ong; Michael Fehlings; Daniel Shao-Weng Tan; Nadiah Binte Sukma; Eileen Xueqin Chen; Jen-Hwei Sng; Connie Siew Poh Yip; Kok Hing Lim; Darren Wan-Teck Lim; Narayanan Gopalakrishna Iyer; et al. (European Thyroid Journal, 2024)
Objective: Anaplastic thyroid cancer (ATC) is an aggressive disease associated with poor outcomes and resistance to therapies. Our study aim was to evaluate the activity of a combinatorial regimen of sandwich sequencing of pembrolizumab immunotherapy and hypofractionated radiotherapy (RT). Methods: In this case series, patients with ATC received hypofractionated RT (QUAD-shot) and intravenous pembrolizumab 200 mg every 3–4 weeks. Pembrolizumab was continued until disease progression or up till 24 months. Concurrent lenvatinib treatment was allowed. Primary endpoint was best overall response (BOR) and progression-free survival (PFS). Additionally, we performed immune profiling of circulating T cells in a responder to investigate the immune response to our combinatorial treatment. Results: At median follow-up of 32.6 months (IQR: 26.4–38.8), of a cohort of five patients, BOR was 80%; with two complete responses (CR) and two partial responses (PR). Patients who achieved CR remained disease-free at last follow-up. Median PFS was 7.6 months (IQR: 6.2–NR), and 1-year PFS and overall survival rate was 40% (95% CI: 13.7– 100) for both. Treatment was well-tolerated, with mostly grade 1–2 adverse events. Immune profiling of one partial responder revealed an increase in activated CD4 and CD8 T cells post-QUAD-shot RT, which was further enhanced during the maintenance phase of pembrolizumab. Conclusion: Herein, we report a case series of five patients with ATC, with two long-term survivors who were treated with surgical debulking followed by QUAD-shot RT and pembrolizumab, possibly due to synergy of local and systemic treatments in activating anti-tumour immunogenic cytotoxicity. This regimen warrants further investigation in a larger cohort of patients.